SMART CITY : KONSEP KOTA CERDAS ERA KONTEMPORER (STUDI KEBIJAKAN SMART CITY DI KABUPATEN SUMENEP) - imam hidayat; Hadi Soetarto (PUBLIC CORNER, 2022)
Abstract Along with the development of the digitalization era, requiring government agencies to take advantage of this potential as a medium in developing the region in a more advanced direction by ensuring the quality of services and good government resources, smart cities are a product of the program after the fall of the new order so that local governments have the power to regulate their regions. independently. The smart city concept itself is expected to be able to answer the challenges of the times along with the rapid world of technology, information or digitalization. It seems that smart cities have been used by local governments in Indonesia, including Sumenep Regency. This study uses a descriptive analysis design by using a qualitative approach to look for symptoms or empirical facts about the existence of a smart city policy in Semenep Regency using a theoretical focus from Pratama (2014), there are six indicators of Smart City success, namely as follows, Smart Economy, Smart People , Smart Governance, Smart Environment, Smart Living. In this study, the collection technique used was observation at the research location, researchers also conducted interviews with informants and continued with documentation. The data analysis technique used in this study uses data reduction, followed by data presentation and conclusion drawing or data verification. The results of research that have been carried out include a) Smart Economy, the government is more intense in encouraging the creation of economic activities by utilizing digital. b) Smart People, collaborative activities with stakeholders as a means of contributing to city development by utilizing technology and information in order to find ideas and designs for the progress of Sumenep Regency. c) Smart Governance, improving the quality of services, both managerial or public information access services, continues to be built and maintained so that the level of public trust in the government is higher. d). Smart Environment, there needs to be an appropriate alternative and solution in preventing environmental problems in Sumenep Regency while still guided by the importance of environmental impact analysis. e). Smart Living, the whole of the obligation to provide public goods and services so that they can be developed in order to be able to adapt to every need of the wider community. Keywords:Smart City, Public Policy Abstrak Seiring dengan berkembangnya era digitalisasi, mengharuskan lembaga pemerintahan untuk memanfaatkan potensi ini sebagai media dalam membangun daerah ke arah lebih maju dengan menjamin kualitas pelayanan dan sumber daya pemerintahan yang baik, smart city adalah produk program pasca jatuhnya orde baru sehingga pemerintah daerah memiliki kekuatan untuk mengatur daerahnya secara mandiri. Konsep smart city sendiri diharapakan mampu menjawab tantangan jaman bersamaan dengan pesatnya dunia teknologi, informasi atau digitalisasi. Nampaknya smart city telah dipakai oleh pemerintah daerah di indonesia tidak terkecuali kabupaten Sumenep. Penelitian ini menggunakan desain analisis deskriptif dengan melakukan pendekatan kualitatif mencari gejala gejala atau fakta empirik tentang keberadaan kebijakan smary city di Kabupaten Semenep dengan menggunakan fokus teori dari Pratama (2014), terdapat enam indikator keberhasilan Smart City, yaitu sebagai berikut, Smart Economy, Smart People, Smart Governance, Smart Environment, Smart Living. Dalampenelitianinimenggunakan Teknik pengumpulanadalahobservasi pada lokasipenelitian, peneliti juga melakukanwawancarakepadainformaninfroman dan dilanjutkandengandokumentasi. Adapun Teknik analisis data yang digubakandalampenelitianinimenggunakanreduksi data, dilanjutkandenganpenyajian data dan penarikankesimpulanatauverifikasi data. Hasil penelitian yang sudahdilakukan, meliputi a) Smart Ekonomy, pemerintahlebihintensdalammendorongterciptanyakegiatanperekonomiandenganpemanfaatan digital. b) Smart People, kegiatankolaborasidengamstakeakholdersebagaisaranadalammemberikansumbangsihbagipembangunankotadenganpemanfaatanteknologi dan informasi agar menemukan ide dan rancanganbagikemajuanKabupatenSumenep. c)Smart Governance, perbaikankualitaspelayananbaikmanajerialataupelayananaksesinformasipublikterusdibangun dan dijaga agar tingkatkepercayaanpublikterhadappemerintahsemakintinggi. d). Smart Environment, perluadaalternatif dan solusi yang tepatdalammencegahmasalahlingkungan di KabulatenSumenepdengantetapberpedoman pada pentingnyaanalisisdampaklingkungan. e).Smart Living, keseluruhandarikewajibanketersediaanbarangpublik dan jasapelayanan agar tetapdikembangkan agar mampumenyesuaikandengansetiapkebutuhandarimasyarakatsecaraluas. Kata kunci : Smart City, Kebijakan Publik